Describing Noncovalent Interactions beyond the Common Approximations: How Accurate Is the "Gold Standard," CCSD(T) at the Complete Basis Set Limit? - Řezáč, Jan; Hobza, Pavel (Journal of chemical theory and computation, 2013)
We have quantified the effects of approximations usually made even in accurate CCSD(T)/CBS calculations of noncovalent interactions, often considered as the "gold standard" of computational chemistry. We have investigated the effect of excitation series truncation, frozen core approximation, and relativistic effects in a set of 24 model complexes. The final CCSD(T) results at the complete basis set limit with corrections to these approximations are the most accurate estimate of the true interaction energies in noncovalent complexes available. The average error due to these approximations was found to be about 1.5% of the interaction energy.